Meristematic shoot tip culture obtain good quality seedling of citrus (Citrus nobilis var. brastepu) free from citrus vein phloem degeneration - Isnaini Nurwahyuni; Justin A. Napitupulu; . Rosmayati; Fauziah Harahap (Syiah Kuala University, 2012)
Meristematic shoot tip culture to obtain good quality seedling of citrus (Citrus nobilis Var. Brastepu) free from citrus vein phloem degeneration (CVPD) is explained in this research. The method is conducted by using a diseased plant and is then propagated in optimum conditions. The research is conduted in Tissue Culture Laboratory Department of Biology, University of North Sumatra, Indonesia. Optimum conditions for citrus propagation have been obtained to produce good quality of Citrus seedlings that is free from CVPD. The analysis of the DNA using PCR method has confirmed that the seedlings are healthy and free from CVPD. Genomic analysis using 10 RAPD markers show the planlets regenerated from the cultures are 100% similar with the mother plant.